2018
DOI: 10.1177/1082013218759364
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thyme and oregano essential oils on the shelf life of salmon and seaweed burgers

Abstract: The effect of different essential oils on the quality and shelf life of fish and seaweed burgers during storage was evaluated. For this purpose, thyme and oregano essential oils were selected at a concentration of 0.05% (v/w). Three types of salmon and seaweed burgers were prepared: without essential oil, burgers with red thyme essential oil (0.05% (v/w)) and burgers with oregano essential oil (0.05% (v/w)), which were vacuum packaged and stored at 4 ℃ for 17 days. Physicochemical and microbiological analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 24 publications
2
25
0
1
Order By: Relevance
“…The initial MTC of BHM samples (before testing) was 3.1 log CFU/g, in accordance with the data reported from fish finger immediately after preparation. 55,56 The MTC of unpacked control samples (lot A) and packed in control film (FG-0CRV, lot B) steadily increased up to the 28 th day. Beyond that time, lot A attained a maximum aerobic bacterial count close to 4.2 log CFU/g, which was below 7 log CFU/g that is considered the onset of spoilage of fish products according to FAO 57 and the International Commission on Microbiological Specifications for Foods (ICMSF).…”
Section: Aerobic Plate Countmentioning
confidence: 99%
“…The initial MTC of BHM samples (before testing) was 3.1 log CFU/g, in accordance with the data reported from fish finger immediately after preparation. 55,56 The MTC of unpacked control samples (lot A) and packed in control film (FG-0CRV, lot B) steadily increased up to the 28 th day. Beyond that time, lot A attained a maximum aerobic bacterial count close to 4.2 log CFU/g, which was below 7 log CFU/g that is considered the onset of spoilage of fish products according to FAO 57 and the International Commission on Microbiological Specifications for Foods (ICMSF).…”
Section: Aerobic Plate Countmentioning
confidence: 99%
“…These results are in accordance with reports by Cofrades et al [36] and Fernandez-Martin et al [37] in burger patties with added seaweeds. However, Dolea et al [38] suggested that the hardness was not modified by the addition of thyme and oregano essential oils in salmon and seaweed burgers. Furthermore, fibers and polysaccharides of Spirulina can also play an important role in modifying the hardness of these processed products.…”
Section: Textural Parametersmentioning
confidence: 99%
“…According to phytochemical studies on the essential oil composition of Origanum vulgare and other related species, there is a wide chemical diversity, with a considerable intraspecific qualitative and quantitative variation in constituents is found [ 13 , 14 , 15 , 16 , 17 ]. Some studies have also reported the potential of oregano essential oil to preserve food such as salmon and seaweed burgers [ 18 ], fish, and meat products [ 19 ]. Different studies on the isolation and characterization of O. vulgare essential oils from different world regions have been performed [ 20 ].…”
Section: Introductionmentioning
confidence: 99%